Design, simulation, analysis and fabrication of a modular face shield for the end users with skull deformity - Thiruchitrambalam, M. (IEEE, 2024)
Craniosynostosis leads to unusual skull shapes in the infants. Genetic factors as well as environmental factors are associated with this type of disorder. During the pandemic Governments will not be able to impose complete lockdown due to economic compulsions. It is necessary to use protective devices such as face shields during the pandemic. This article describes development of a modular face shield using 3D printing method that meets the needs of the end user’s with highly deformed skulls.
uGDX
Keywords: 3D Printing; Pugh’s Design Concept Marix; CFD analysis; Face shield; COVID-19; SARS; Design Patent